TEMPORAL TREND OF HIV/AIDS INCIDENCE AND MORTALITY IN BRAZIL, FROM 2009 TO 2019 - Ellwanger, Maurício Pratzel; Ellwanger, Manuela Pozza; Diogo, Fabiley de Wite; de Oliveira, Liz Andréa Babireski Braz; Reinert, Debora; Diogo, Águida Vita de Souza; Munhoz, Antônio Carlos Mattar; Marcon, Chaiana Esmeraldino Mendes (Anais New Science Publishers | Editora Impacto, 2024)
Objectives: To analyze the temporal trend of HIV/AIDS incidence and mortality in Brazil from 2009 to 2019, identifying regional and demographic variations. Methods: An ecological time series study using data from the Notifiable Diseases Information System (SINAN) and the Mortality Information System (SIM) of the Ministry of Health. Incidence and mortality rates were calculated for the period from 2009 to 2019. The analysis of temporal trends was performed using linear regression for time series, with a statistical significance level of 95% (p < 0.05). Results: During the study period, 448,682 new cases of HIV and 132,499 AIDS-related deaths were recorded in Brazil. The South and Southeast regions had the highest incidence and mortality rates. The highest rates were observed in males and in the 30-39 age group. The main cause of death, according to the ICD-10, was related to infectious and parasitic diseases. There was a general trend toward a reduction in HIV/AIDS incidence and mortality during the study period. Conclusions: The study identified a trend of reduction in HIV/AIDS incidence and mortality in Brazil between 2009 and 2019, highlighting important regional and demographic variations. These results suggest the effectiveness of public policies, government interventions, and medical advances, such as antiretroviral therapy (ART), in reducing mortality and incidence of the disease.